Exploring the Dimensions of Pilgrims’ Experiences - A. S., Sathish; Venkatesakumar, Ramakrishnan (Indian Journal of Marketing, 2014)
Purpose: Experiences are private events that occur in response to some stimulation. They often result from direct observation or participation in events - whether they are real, dreamlike, or virtual. This study aims to understand and explore the dimensions of pilgrims’ experiences at Tirumala Tirupati Devasthanam (TTD) located in Tirumala near Tirupati in Andhra Pradesh. Furthermore, the study aimed to develop an instrument that would measure the pilgrims’ experiences. Approach: The current trend in the marketing practices is to create engaging and lasting experiences for the customers. To understand the experiences in the services context, the study was conducted with the pilgrims who visited the holy Tirumala temple. A self administered questionnaire which included both structured and open-ended questions was used. Findings: A close look out for the various dimensions of pilgrims’ experiences management was developed and an instrument to measure pilgrims’ experiences in the context of the holy temple was evolved. Research Limitations: The research scope registered only exceptional experiences of the respondents and experiences observed at the time of the study. The grade of criticality of the experiences was not examined further. Practical Implications: The study provides a new understanding of pilgrims’ experiences and would help the temple management to design a framework that enhances the darshan experience and ensures that the pilgrims have a memorable stay at the Tirumala temple. Originality/Value: This paper is the first of its kind, exploring the various dimensions of pilgrims’ experiences and addressing the dimensions that create the various aspects of a wonderful darshan leading to the pilgrims being satisfied with their visit.